Potential plant species for live pole application in tropical environment - Mafian, Sasan; Kim Huat, Bujang; A. Rahman, Nordin; Singh, Harwant (Science Publications, 2009)
Problem statement: Slope instability causing landslides, a major geologic hazard, is a risk common to most regions. Among all categories of landslides, shallow slope failures which affect many hill slopes and earthwork projects are the most wide spread and pose the most costly maintenance problem. One of the soil improvement methods that seem suitable for preventing shallow slope failures is the Live Pole technique. Approach: Due to the geographical variability in the application of this technique in different regions this study was carried out in a tropical environment. Results: This study initially describes the requirement for suitable live poles in tropical regions utilizing indigenous woody species and potential candidates. It then describes screening tests trials that these species were put through to observe their propagation from large live cuttings obtained from branches of small trees and shrubs, viz., tests for root and stem growth in a controlled medium under shade-house conditions with irrigation and then discusses the results of these for their suitability for field trials by replanting in selected natural soils. Conclusion/Recommendations: The results of these screening tests found two species, namely, Hibiscus tiliaceus (Ht/i>) and Dillenia suffructicosa (Ds) which met the requirements for field test trials.